Long-term care facilities' response to the COVID-19 pandemic: An international, cross-sectional survey - Eltaybani, Sameh; Igarashi, Ayumi; Cal, Ayse; Lai, Claudia K. Y.; Carrasco, Cristina; Sari, Dianis Wulan; Cho, Eunhee; Haugan, Gørill; Bravo, Jorge D.; Abouzeid, Nesreen A.; Wachholz, Patrick Alexander [UNESP]; Isaramalai, Sang-arun; et al. (Wiley, 2024)
Aims: To (i) assess the adherence of long-term care (LTC) facilities to the COVID-19 prevention and control recommendations, (ii) identify predictors of this adherence and (iii) examine the association between the adherence level and the impact of the pandemic on selected unfavourable conditions. Design: Cross-sectional survey. Methods: Managers (n = 212) and staff (n = 2143) of LTC facilities (n = 223) in 13 countries/regions (Brazil, Egypt, England, Hong Kong, Indonesia, Japan, Norway, Portugal, Saudi Arabia, South Korea, Spain, Thailand and Turkey) evaluated the adherence of LTC facilities to COVID-19 prevention and control recommendations and the impact of the pandemic on unfavourable conditions related to staff, residents and residents' families. The characteristics of participants and LTC facilities were also gathered. Data were collected from April to October 2021. The study was reported following the STROBE guidelines. Results: The adherence was significantly higher among facilities with more pre-pandemic in-service education on infection control and easier access to information early in the pandemic. Residents' feelings of loneliness and feeling down were the most affected conditions by the pandemic. More psychological support to residents was associated with fewer residents' aggressive behaviours, and more psychological support to staff was associated with less work–life imbalance. Conclusions: Pre-pandemic preparedness significantly shaped LTC facilities' response to the pandemic. Adequate psychological support to residents and staff might help mitigate the negative impacts of infection outbreaks. Impact: This is the first study to comprehensively examine the adherence of LTC facilities to COVID-19 prevention and control recommendations. The results demonstrated that the adherence level was significantly related to pre-pandemic preparedness and that adequate psychological support to staff and residents was significantly associated with less negative impacts of the pandemic on LTC facilities' staff and residents. The results would help LTC facilities prepare for and respond to future infection outbreaks. Patient or public contribution: No Patient or Public Contribution.
Keywords: adherence; aged; compliance; COVID-19; long-term care; multilevel analysis; older adults